IMPLEMENTASI METODE KOLASE DALAM MENINGKATKAN MOTORIK HALUS ANAK USIA DINI - Suseni, Made; Arini, Ni Made; Sasmika Dewi, Ni Putu (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2021)
Improve Early Childhood Education, teachers must have high creativity in delivering material using methods that make children motivated to learn. One of them is the collage method which aims to improve fine motor skills in early childhood. This study uses qualitative and descriptive methods with data collection techniques by triangulation, observation, interviews, and documentation. The collage method applied at Cahaya Ananda Kindergarten uses various media such as paper, seeds, cotton.